Efektifitas Pedoman Program Latihan Kebugaran Berbasis Kearifan Lokal Malind Anim Sebagai Media Literasi Dalam Meningkatkan Pola Hidup Sehat Pada Korban Penyalahgunaan Napza Di Perbatasan RI-PNG - Arifin Ika Nugroho; Emanuel Lewar; Damaris Marlissa (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
This study aims to determine: The Effectiveness of the Guidelines for the Malind Anim Local Wisdom-Based Fitness Exercise Program as a Literacy Media In Improving Healthy Lifestyles in Drug Abuse Victims at the RI-PNG Border, and differences in people's fitness levels, between the use of Malind Anim Local Wisdom-Based Fitness Exercise Program Guidelines as Media Literacy in Improving Healthy Lifestyles with the use of random material sources. The method used in this study is an experimental method, in the form of a Quasi Experiment, namely the Nonrandomized Control Group Pretest-Posttest Design. The subject of this research is the people of Kampung Yanggandur who are included in the research criteria. The methods used to collect data are test and non-test instruments. This research will answer the differences in community fitness levels, between the use of Malind Anim Local Wisdom-Based Fitness Exercise Program Guidelines as Media Literacy in Improving Healthy Lifestyles and the use of random material sources. The effectiveness of the use of the Guidelines for the Malind Anim Local Wisdom-Based Fitness Exercise Program on Drug Abuse Victims at the RI-PNG Border is not yet used by the community. Based on the results of posttest data calculations, the researchers concluded that an increase in VO2 Max could be increased by using the Cooper test. Besides that, it can also be seen by the results of calculating a significance value of 0.000. It can be concluded that the product in the form of a fitness training program guideline for drug abuse victims that has been developed is effective in increasing the fitness of drug abuse victims. Keywords: Exercise Guidelines, Drugs, OGPZ